2022
DOI: 10.1093/plphys/kiac184
|View full text |Cite
|
Sign up to set email alerts
|

Building an extensible cell wall

Abstract: This article recounts, from my perspective of four decades in this field, evolving paradigms of primary cell wall structure and the mechanism of surface enlargement of growing cell walls. Updates of the structures, physical interactions, and roles of cellulose, xyloglucan, and pectins are presented. This leads to an example of how a conceptual depiction of wall structure can be translated into an explicit quantitative model based on molecular dynamics methods. Comparison of the model’s mechanical behavior with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
114
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 404 publications
0
114
0
Order By: Relevance
“…Hemicelluloses and pectins, also known as matrix polysaccharides or cross-linking glycans are synthesized in the Golgi apparatus and are transported via vesicles to the developing the cell plate. Hemicelluloses bind to cellulose microfibres pectin a soft network with extensive but weak contacts to cellulose and xyloglucan in mature cell wall [84], thus their timely deposition and assembly are essential for a functional cell wall network. Our current understanding of the delivery and assembly of these polysaccharides into the developing cell plate and cell wall is limited and mostly derived from studies using electron microscopy coupled with immunolocalization with polysaccharide specific antibodies [85][86][87][88][89][90][91].…”
Section: Non-cellulosic Polysaccharides and Glycoproteinsmentioning
confidence: 99%
“…Hemicelluloses and pectins, also known as matrix polysaccharides or cross-linking glycans are synthesized in the Golgi apparatus and are transported via vesicles to the developing the cell plate. Hemicelluloses bind to cellulose microfibres pectin a soft network with extensive but weak contacts to cellulose and xyloglucan in mature cell wall [84], thus their timely deposition and assembly are essential for a functional cell wall network. Our current understanding of the delivery and assembly of these polysaccharides into the developing cell plate and cell wall is limited and mostly derived from studies using electron microscopy coupled with immunolocalization with polysaccharide specific antibodies [85][86][87][88][89][90][91].…”
Section: Non-cellulosic Polysaccharides and Glycoproteinsmentioning
confidence: 99%
“…And yet, considering the importance of the cell wall, it remains relatively poorly understood. This is partly due to its sheer complexity – the cell wall is a heterogeneous biopolymer made of dozens of different polysaccharides, phenolics, and proteins woven together into a structure that is recalcitrant to chemical digestion and, therefore, difficult to investigate (Cosgrove, 2022).…”
Section: Figurementioning
confidence: 99%
“…In vitro assays showed that PME activity is attenuated at low pH and that interactions of PME with pectin methyl-esterase inhibitors (PMEIs) are stabilized (Hocq et al, 2017a). Despite their importance as components of the CW, there is still a gap of information on the effects of PME and PMEI on growth processes and contradictory results have been published on the effects of those proteins (Jonsson et al, 2022; Cosgrove, 2022). Whilst some authors reported increased stiffness and shorter cells in the hypocotyl of lines overexpressing pectin methylesterases (Bou Daher et al, 2018), others have shown decreased stiffness and increased cell size (Peaucelle et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro assays showed that at low pH interaction of PMEIs with PMEs is stabilized and the PME activity attenuated (Hocq et al, 2017a). De-methylesterified pectins have free carboxyl groups that are hypothesized to either form cross-links mediated by calcium ions (the so called egg-box hypothesis), which might increase the rigidity of the CW (Hocq et al, 2017b), or undergo cleavage to shorter HGs chains resulting in the softening of the CW (Cosgrove, 2022). Based on super-resolution microscopy, it has been described that pectins possibly form nanofilaments that alter their quaternary structure upon de-methylesterification and calcium cross-linking, supporting the egg-box model (Haas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation